Double Predestination View By John Calvin, In His Commentaries And Institutio Book - Elisabeth Sulastri (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
This article discusses the teaching view of John Calvin about Double Predestination. Any Bible verses that are the basis of explaining this teaching. The explanation of these verses can be the basis for understanding the teaching of John Calvin about Double Predestination. There are three topic discussions in this article, First Double Predestination View by John Calvin, second in His Commentaries, and third institution book. May this article provide new insight and enlightenment for every reader.